Desenvolvimento do capitalismo no Brasil e as tendências da política de saúde - Costa, Laila Talita da Conceição; Méllo, Lívia; Nogueira, Priscila Tamar Alves (Saúde e Sociedade, 2019)
The public health policy constitutes an instrument in permanent power dispute, and the growing appropriation of its services by the private market is evidencing the different corporate projects that are in confrontation within the Brazilian State. However, the political domination of a social class through the State can not be explained only by records of state action in a given period, that is, by the simple reflection of the development of the mode of production. It is rather the result of the movement of contradictions that can only be seen in the field of class struggle, in the correlation of forces existing in civil society. Thus, this study aims at analyzing the trends of the public health policy, taking into account the current characteristics of the political-economic development of the Brazilian State, but also situating it as a social policy inscribed in the complex relationships that involve the production and reproduction process of contemporary capitalism.